PENGARUH PENGANGGARAN PARTISIPATIF TERHADAP KINERJA MANAJERIAL DENGAN KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN SEBAGAI VARIABEL MODERASI (Survei pada Pegawai Satuan Kerja Perangkat Daerah Kabupaten Sragen) - Muhammad Rofiq Sunarko, Vera Putri Meliya Sari, Bambang Widarno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
Budget on local government organizations related to their use in determiningthe amount of the portion of the funds to finance programs and activities from fundsbelonging to the people. The use of funds belonging to the people in the public sectorbudget formulation requires that the drafters of the budget should focus on thewelfare of society. The purpose of this study was to analyze the significance of theeffects of participatory budgeting and management accounting systemcharacteristics the performance of employees in Satuan Kerja Perangkat Daerah(SKPD) Sragen. Analyzing the characteristics of the moderating effects ofmanagement accounting system in participative budgeting influence the performanceof employees in Satuan Kerja Perangkat Daerah Sragen. This study used surveymethods, the type of data used quantitative and qualitative data, the data source usedprimary data and secondary data. The population in this study were all Leader/Headof Division/Head of Sub Division/Section Head in Satuan Kerja Perangkat DaerahSragen totaling 473 people. The number of samples in the study 92 sample, bysampling using accidental sampling. Data collection methods are used:questionnaires and documentation. Data analysis technique used to test the validity,reliability test, classic assumption test and multiple linear regression analysis andtest of absolute difference. In conclusion that: 1) There is significant influence onemployee performance participatory budgeting at the Satuan Kerja Perangkat DaerahSragen. 2) There was a significant effect of management accounting systemcharacteristics the performance of employees in Satuan Kerja Perangkat DaerahSragen. 3) Characteristics of accounting management system of participatorybudgeting moderating influence on the performance of employees in Satuan KerjaPerangkat Daerah Sragen.Keywords: participatory budgeting, management accounting system characteristics,employee performance